Dinotoperla walkeri sp. nov. (Plecoptera: Gripopterygidae), a brachypterous stonefly from western Victoria, Australia - Dean, John; St Clair, Ros (Zootaxa, 2006)
A new brachypterous species of stonefly (Dinotoperla walkeri sp. nov.) is described from Hopkins Falls in western Victoria. The species is large compared to other species of the genus, and the robust nymph is adapted to live on or under boulders in fast currents. Such conditions appear not to occur elsewhere in the region of the type locality, and it is speculated that brachyptery may be an adaptation which ensures that adults do not disperse away from the nymphal habitat.